CFD Simulation Of Cooperative AUV Motion. - Husaini, Muhamad; Samad, Zahurin; Arshad, Mohd Rizal (2008)
Cooperative AUV performance and efficiency is directly related to its power efficiency. The power consumption for this type of underwater vehicle is influenced by its motion needed because most of the power is spent for thruster to produce thrust.